Dynamic government performance: honeymoons and crises of confidence - Myatt, D; Dewan, T (University of Oxford, 2010)
We model the interplay between a government's performance, its expected lifetime, and the confidence it enjoys. Here, "confidence" can be broadly interpreted as the government's popularity, the size of its parliamentary majority, its reserve of talent, or other factors. Confidence evolves in response to performance, and if it evaporates then the government falls. We analyze how confidence influences ministers' behavior. A minister's tenure is determined by the performance of both himself and others. He chooses higher performance when the government is expected to last, which is so when others perform well. Multiple equilibria arise: in an optimistic equilibrium, high performance sustains a government indefinitely; in a pessimistic equilibrium, the government's expected demise is a self-fulfilling prophecy. When confidence evolves stochastically, however, there is a unique equilibrium in which a crisis of confidence begins if and only if negative shocks shift confidence below a critical threshold.